Effects of 8 weeks of combined strength and plyometric training on lower limb vertical stiffness and jump performance in elite long jump athletes - Xu, Zhanming; Sun, Jiawei; Gu, Jianing; Yu, Laikang (Frontiers in Physiology, 2025)
BackgroundThe approach run in the long jump relies heavily on lower limb vertical stiffness and elastic energy utilization (EEU). While conventional strength training enhances maximal force, it may not adequately improve stiffness or stretch-shortening cycle efficiency. Plyometric training (PT), by contrast, specifically targets these qualities. This study examined whether combining strength and plyometric training yields superior neuromuscular adaptations in elite long jump athletes.MethodsTwenty-four elite long jump athletes (12 male, 12 female) were allocated to a strength training group (ST) or a combined strength plus plyometric training group (ST + PT). Both groups trained twice weekly for 8 weeks, with ST loads set at 80%–85% one-repetition maximum (1RM). Outcome measures included 1RM back squat strength, countermovement jump (CMJ) height, vertical stiffness (Kvert, bilateral and unilateral), and EEU.ResultsBoth the ST and ST + PT interventions significantly improved 1RM strength in elite long jump athletes (P < 0.001). However, significant enhancements in vertical stiffness (Kvert-L, Kvert-R, Kvert-B; P < 0.01), EEU (P < 0.05), and CMJ height (P < 0.01) were observed exclusively in the ST + PT group. Furthermore, male athletes demonstrated greater training-induced adaptations than females, particularly in 1RM (P < 0.001), vertical stiffness (Kvert-R, P = 0.010; Kvert-B, P = 0.001), and CMJ height (P = 0.003).ConclusionAn 8-week program combining strength and plyometric training is more effective than strength training alone for enhancing lower-limb stiffness, EEU, and jump performance in elite long jump athletes, particularly in males. These findings support integrating plyometric modalities into pre-competition training cycles.